Evaluación y control de síntomas en oncología pediátrica: una necesidad que cubrir y un mundo por descubrir - Salas, Maitane; Gabaldón, Olga; Mayoral, José Luis; Arce, Mila; Amayra, Imanol (Psicooncología, 2004)
Children with cancer experience symptoms related to illness and/or treatment. Symptom experiences in the child with cancer are individual, subjetive and they change over time. There is still much to be discovered about how children with cancer and their families experience childhood cancer symptoms. In this article, how children and their families experience symptoms is described, and the literature about some frequent symptoms experienced by child with cancer, including pain, fatigue and chemotherapy related nausea and vomiting, is reviewed, addressing psychological techniques used in the treatment of these symptoms. Finally, there is a reflexion about pediatric psychooncologist role in the assessment and management of physical symptoms in pediatric oncology patient, and about the need of research in symptom assessment and control.